GOT1/AST1 expression status as a prognostic biomarker in pancreatic ductal adenocarcinoma - Feld, Fenja M.; Nagel, Philipp D.; Weissinger, Stephanie E.; Welke, Claudia; Stenzinger, Albrecht; Möller, Peter; Lennerz, Jochen K. (OncoTarget, 2015)
Prognostication in pancreatic ductal adenocarcinoma (PDAC) remains a challenge. Recently, a link between mutated KRAS and glutamic-oxaloacetic transaminase (GOT1/AST1) has been described as part of the metabolic reprogramming in PDAC. The clinical relevance of this novel metabolic KRAS-GOT1 link has not been determined in primary human patient samples. Here we studied the GOT1 expression status as a prognostic biomarker in PDAC. We employed three independent PDAC cohorts with clinicopathological- and follow-up data: a) ICGC, comprising 57 patients with whole-exome sequencing and genome-wide expression profiling; b) ULM, composed of 122 surgically-treated patients with tissue-samples and KRAS status; c) a validation cohort of 140 primary diagnostic biopsy samples. GOT1 expression was assessed by RNA level (ICGC) or immunolabeling (ULM/validation cohort). GOT1 expression varied (ICGC) and correlation with the KRAS mutation- and expression status was imperfect (P = 0.2, ICGC; P = 0.8, ULM). Clinicopathological characteristics did not differ when patients were separated based on GOT1 high vs. low (P = 0.08–1.0); however, overall survival was longer in patients with GOT1-expressing tumors (P = 0.093, ICGC; P = 0.049, ULM). Multivariate analysis confirmed GOT1 as an independent prognostic marker (P = 0.009). Assessment in univariate (P = 0.002) and multivariate models in the validation cohort (P = 0.019), containing 66% stage IV patients, confirmed the independency of GOT1.